La villa du Liégeaud et ses peintures La Croisille-sur-Briance (Haute-Vienne) - Dumasy-Mathieu, Françoise (Documents d'archéologie française, 1991)
The paintings discovered during excavation of this villa in the Limousin constitue a unicum in the context of the residential architecture of Roman Gaul. The most interesting of them commemorate a performance in the amphitheatre (figures of gladiators and venatores, scenes showing the spectators and the pompa witch opens the minus) and give the name of the benefactor, Romulus, owner of the villa, whose munificence has provided the performance. The study is completed by a history of the main dwelling-house through the successive transformations of this ground-plan and décor. This publication provides an exceptionally valuable illustration of the life and behavior of local Gallo-Roman notables during the IInd century AD